(untitled) - Newman, John M. (New York, 1992)
Deception, intrigue, and the struggle for power of John Fitzgerald Kenendy, stages 1961-1963
Keywords: United States,Hoa Kỳ,Kenendy, John Fitzgerald,Tổng thống John Fitzgerald Kenendy; Politics and Government,Chính trị và chính phủ; 1961-1973,1961-1973